UPAYA PENINGKATAN ANGKA BEBAS JENTIK (ABJ) DBD MELALUI PENGGERAKAN JUMANTIK (Unnes Journal of Public Health, 2013)
Dengue Hemorrhagic Fever (DHF) is a disease that the number of sufferers is increasing every year. Issues that were examined in this study is an effort to increase Larva-Free Numbers DHF through Larva Monitoring interpreter mobilization. The purpose of this study was to determine the difference between the ABJ DBD before and after mobilization jumantik in RW I Danyang Village Sub District Of Purwodadi Grobogan. This research was a pre-experimental research design using the design of one group pretest-posttest design. This research used cluster random sampling. Total sample was 231 households. Based on the Wilcoxon test showed that there were significant differences between the ABJ DBD before and after mobilization jumantik with p value (0.000) < Î± (0.05). The conclusion of this research was mobilizing jumantik can increase your ABJ DBD in RW I Danyang Village Sub District Of Purwodadi Grobogan Advice to the public immediately mosquito nest eradication and actively participated incounseling. To expect the government to make policies that involve the community in the prevention and eradication of dengue through a more effective methods..